Taxonomy of the Proisotoma complex. Redefinition of genera and description of new species of Scutisotoma and Weberacantha(Collembola, Isotomidae) - Potapov, Mikhail; Babenko, Anatoly; Fjellberg, Arne (Zootaxa, 2006)
The paper provides new information on morphological characters which are useful in generic diagnostics of the Proisotoma complex of Isotomidae. Based on this information, a number of known species are excluded from the redefined Proisotoma s. str. and moved to the genus Scutisotoma Bagnall, 1949, which is again given generic status. The following genera are given more precise definitions: Subisotoma Stach, 1947, Ballistura Börner, 1906, Proisotoma Börner, 1901 and Weberacantha Christiansen, 1951. A new genus, Strenzketoma, is erected for the species “Proisotoma” buddenbrocki Strenzke. Scutisotoma titusi (Folsom), S. muriphila (Grinbergs), and S. ladaki (Denis) are redescribed. Fourteen new species of the genus Scutisotoma (S. acorrelata sp.n., S. baica sp.n., S. dodecocellata sp.n., S. indigirka sp.n., S. karadagi sp.n., S. kolymica sp.n., S. longisensilla sp.n., S. matalini sp.n., S. millimetrica sp.n., S. montana sp.n., S. nicksmeti sp.n., S. schisti sp.n., S. stachanoremi sp.n., S. tenuidentifera sp.n.) and two new species of Weberacantha (W. echinodermata sp.n., W. magnomucrella sp.n.) are described. Types of S. ananevae (Babenko & Bulavintsev), S. armeriae (Fjellberg), S. christianseni (Stach), S. oirota (Vilkamaa), S. stepposa (Martynova), S. tianshanica (Martynova), and S. tolerans (Babenko) have been studied. Keys to genera and to the known Holarctic species of Scutisotoma Bagnall and Weberacantha Christiansen are given.